Application Of Edible Surface Coatings To Prolong The Storage Life Of Baramasi Lemon (Citrus Limon L. Burm) Fruits (Applied Biological Research, 2018)
Mature light green, uniform and healthy fruits of Baramasi lemon (Citrus  limon L. Burm) cv. PAU Baramasi lemon-1 were coated with different  concentrations (0.25, 0.50 and 0.75%) of chitosan, carboxymethyl cellulose and  Aloe veragel to analyze their effects on storage life and fruit quality. Fruits  were analyzed after 15, 30, 45 and 60 days for various physicochemical  parameters. Physiological loss in weight increased with increase in storage  period, whereas peel thickness and vitamin-C content declined with the  extension of storage period. Other parameters like juice percentage and  titratable acidity showed an increasing trend during initial stages of storage,  but at the end of storage a decline was observed. Chitosan @ 0.75% was found  most effective to enhance the storage life of Baramasi lemon fruits up-to 45  days at low temperature storage by reducing physiological loss in weight,  maintaining high peel thickness, juice content, acidity and vitamin- C content.
Keywords: Aloe vera gel; Baramasi lemon; carboxymethyl cellulose; chitosan; storage life